(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Under the accumulation of classroom praxis, artistic education is generally reduced to the teaching of music and the visual arts. In Colombia, Law 115 of 1994 has shown that in official educational institutions, a design of artistic education as space – island – disconnected from other spaces of student learning, omitting what is reflected in the articles of the referenced law, which requires the transversality of the arts with other areas and, therefore, artistic education has a risk in educational institutions of being assigned as the area to cover the workload of educators; Without serious evaluation, respect for the specific knowledge and suitability of the educator according to studies and pre-knowledge in the plastic arts and artistic education. The above implies that the student must be subjected to subjective methods according to each educator and institution. The research methodology is supported within the qualitative paradigm located in the classroom, seeking to map the difficulties manifested in the students such as repetition of their classmates’ words to describe what is reflected in their artistic works, and the systematic presence of textual words without relating from the basic concepts of its school context.